Low-Molecular-Weightt Polysaccharides From Pyropia yezoensis Enhance Tolerance of Wheat Seedlings (Triticum aestivum L.) to Salt Stress - Zou, Ping; Lu, Xueli; Jing, Changliang; Yuan, Yuan; Lu, Yi; Zhang, Chengsheng; Meng, Lei; Zhao, Hongtao; Li, Yiqiang (Frontiers in Plant Science, 2018)
Soil salinity is a serious problem one of the major issues worldwide that affects plant growth and reduces agricultural productivity. Seaweed polysaccharides have been shown to promote crop growth and improve the resistance of plant to induce plant resistance to abiotic stresses. Pyropia yezoensis is a commercially important edible red alga in Southeast Asia. However, there is little research on the application of polysaccharides from P. yezoensis in agriculture. The molecular weight of polysaccharides influences their properties. Therefore，in this study, four representative polysaccharides from Pyropiayezoensis P. yezoensis (PP) with different molecular weights (MW: 3.2 kDa, 10.5 kDa, 29.0 kDa and 48.8 kDa) were prepared by microwave-assisted acid hydrolysis. The relationship between the degradation of polysaccharides from P. yezoensis (DPP) and their effects on plant salt tolerance was investigated. The results showed that exogenous PP and DPPs increased wheat seedling shoot and root lengths, and fresh and dry weights, alleviated membrane lipid peroxidation, increased the chlorophyll content and enhanced antioxidant activities. The expression level examination analysis of several Na+/K+ transporter genes suggested that DPPs could protect plants from the damage of salt stress by coordinating the efflux and compartmentation of Na+. The results demonstrated that polysaccharides could protect plants from salt stress damage by regulating regulate antioxidant enzyme activities and modulatinge intracellular ion concentration, thereby protect plants from salt stress damagethe levels of permeable substances. Furthermore, there was a significant correlation between the tolerance of wheat seedlings to salt stress and MW of polysaccharides. The results suggested that the lower-MW samples (DPP1, 3.2 kDa) most effectively protect wheat seedlings against salt stress.